Virtual Reality as an innovative support in distance education - Sandoval-Poveda, Ana María; Tabash-Pérez, Farith (Innovaciones Educativas, 2021)
Virtual Reality (VR) is an innovative option that can be used to generate potentially significant teaching resources and materials for students belonging to the distance education system. VR is referenced, in documents such as the Horizon 2019 Report, as one of the technologies that higher education must develop and use, in such a way that, three years from that date, it will be of common use and of benefit to the student body. The Universidad Estatal a Distancia (UNED) (State Distance University) worked with this technology in prototypes aimed at students from different schools and majors. These prototypes presented differences that allowed validating the work processes and the construction tools of the resources, in such a way that it is possible to determine which are the most appropriate for each type of requirement. The UNED is prepared to define the best course of action to implement VR according to the needs of the student population studying in the distance modality, the available materials and the different software to work with said technology.